Catalytic Combustion of Methane over CuO/ZrO2-Al2O3 Catalysts Modified by MxOy (M = Y, Cr, Mg, Ce) - Zheng, Shu; Guo, Hong-Xia; Jia, Feng-Chun (Asian Journal of Chemistry, 2013)
A series of CuO/ZrO2-Al2O3 catalysts modified by MxOy(M = Y, Cr, Mg, Ce) have been prepared using sol-gel method. The catalysts have been characterized by BET and XRD techniques and catalytic activity for methane combustion have been investigated. The result of catalytic activity indicates that CuO/Y2O3-ZrO2-Al2O3 catalyst has higher catalytic activity and the best thermal stability. The addition of Y2O3 can increase catalytic activity and thermal stability of CuO/ZrO2-Al2O3 catalyst.